PATH-66. THE GENOMIC LANDSCAPE OF SPINAL CORD EPENDYMOMA. (11th November 2019) - Ramani, Biswarathan; Villanueva-Meyer, Javier; Glastonbury, Christine; Meram, Ece; Walsh, Kyle; Taylor, Jennie; van Ziffle, Jessica; Onodera, Courtney; Grenert, James; Bollen, Andrew; Perry, Arie; Tihan, Tarik; et al.
Abstract: INTRODUCTION: Ependymomas are seen throughout the neural axis but spinal cord is most common in adults. A subset arises in the setting of neurofibromatosis 2, whereas most are sporadic, potentially with somatic NF2 inactivation. The genetic drivers in NF2 wildtype tumors are unknown, as is the spectrum of cooperating genetic alterations. METHODS: We performed targeted next-generation sequencing (NGS) to assess mutations, rearrangements, and chromosomal copy number alterations in 46 adult spinal cord ependymomas. RESULTS: The 24 females and 22 males ranged from 20–73 (median 46) years of age. Tumors were in the cervical (n=24), thoracic (n=12), and lumbar (n=10) spinal cord. Nine tumors (20%) harbored truncating NF2 mutations with loss of the remaining wildtype allele, with frequent monosomy 13q. Thirteen NF2-wildtype tumors (28%) showed monosomy 22q with frequent monosomy 13q and trisomy 7, 9, and 12. Seventeen tumors (37%) carried a near-tetraploid genome, likely due to genomic reduplication with frequent preservation of diploidy in chromosomes 13q (77%), 14q (88%), 21q (53%) and 22q (65%). Remaining cases did not show a recurrent pattern, but one harbored focal high-level MYCN amplification. Three of the six recurrences were seen in the last subgroup; however, there was no significant difference for progression-free survival between four subgroups. None of the NF2 -mutant tumors were in lumbar spinal cord, but there was no difference for tumor location or patient age between four subgroups. DISCUSSION: Biallelic NF2 mutational inactivation characterizes only a subset of spinal cord ependymomas, and MYCN amplification is likely a genetic driver in a small subset of NF2 wildtype cases. The high frequency of chromosome 22q loss even in NF2 -wildtype tumors raises the possibility of cryptic alterations in the NF2 gene not detected by our panel, or perhaps implicates the presence of another as yet unidentified tumor suppressor gene on chromosome 22q.